Factors that influence the company performance: a study at distribution department of Tenaga Nasional Berhad (TNB) Bera / Nur Alia Amira Osman Ali - Osman Ali, Nur Alia Amira (Bachelor of Business Administration (Hons) Marketing, 2015)
Purpose - Increasing number of the debt rate among the consumers lead to a serious loss against Tenaga Nasional Berhad and effects on the company performance; thus, this study was conducted to identify what are the factors that may influence the company performance. Design/methodology/approach – sixty respondents were assigned to answer the designated questionnaire based on the relevant independents variables consisted of employees’ motivation, sufficient training and effective information system. Findings – Result showed that the sufficient training is the most influential factor in this study based on the multiple regression analysis carried. Therefore, it can be concluded that there are many other factors that may truly explain the dependent variable which is the company performance